2011
DOI: 10.1186/1744-8069-7-70
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Adenosine Monophosphate-Activated Protein Kinase (AMPK) in Preclinical Models Reveals a Potential Mechanism for the Treatment of Neuropathic Pain

Abstract: Neuropathic pain is a debilitating clinical condition with few efficacious treatments, warranting development of novel therapeutics. We hypothesized that dysregulated translation regulation pathways may underlie neuropathic pain. Peripheral nerve injury induced reorganization of translation machinery in the peripheral nervous system of rats and mice, including enhanced mTOR and ERK activity, increased phosphorylation of mTOR and ERK downstream targets, augmented eIF4F complex formation and enhanced nascent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
288
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(313 citation statements)
references
References 64 publications
24
288
1
Order By: Relevance
“…It will be interesting to perform an unbiased, comparative assessment of differential downstream target engagement in neural stem cells following chronic rapamycin and metformin treatment. Finally, differences in the response of the IRS/Akt or Grb10 feedback loops ( pain by the simultaneous attenuation of both mTOR and ERK signaling (Melemedjian et al 2011;Tillu et al 2012). In contrast, we observe that both pharmacological and genetic inhibition of mTORC1 evokes spontaneous pain, mechanical hypersensitivity, and increased sensory neuron excitability (Melemedjian et al 2013).…”
Section: Discussionmentioning
confidence: 67%
“…It will be interesting to perform an unbiased, comparative assessment of differential downstream target engagement in neural stem cells following chronic rapamycin and metformin treatment. Finally, differences in the response of the IRS/Akt or Grb10 feedback loops ( pain by the simultaneous attenuation of both mTOR and ERK signaling (Melemedjian et al 2011;Tillu et al 2012). In contrast, we observe that both pharmacological and genetic inhibition of mTORC1 evokes spontaneous pain, mechanical hypersensitivity, and increased sensory neuron excitability (Melemedjian et al 2013).…”
Section: Discussionmentioning
confidence: 67%
“…It has been shown that AMPK pathway is closely associated with nerve regeneration and neuropathic pain (Melemedjian et al, 2011;. Previous study has shown that activation of AMPK might reduce inflammatory nociception (Russe et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that metformin might inhibit injury-induced neuropathic pain through adenosine monophosphate-activated kinase (AMPK) pathway (Melemedjian et al, 2011). Metformin has also been shown to reverse mechanical allodynia in lumbar radiculopathy pain induced by spinal nerve ligation in rats and nerve injury in mice (Taylor et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…4,11,27,28,34 Thus, we investigated the antipruritic action of CCI-779 and metformin, a drug widely given to treat type 2 diabetes and recently shown to inhibit mTORC1 signaling through AMPK pathway found in many cell types including neurons. 6,8,26 2. Materials and methods…”
Section: Introductionmentioning
confidence: 99%